Evidence of Authorship on Messages in Facilitated Communication: A Case Report Using Accelerometry - Faure, Patrick; Legou, Thierry; Gepner, Bruno (Frontiers in Psychiatry, 2021)
Facilitated communication (FC) belongs to alternative and augmentative methods of communication. Currently, FC is very scarcely and unofficially used with people suffering verbal/communicative disorders or neurodevelopmental disorders such as intellectual deficiency or autism spectrum disorder (ASD). FC consists in physical support exerted by a facilitator at hand/wrist/forearm/elbow of a patient/participant, aimed at helping him/her to point at pictures/words, and sometimes to type letters/words on a keyboard. Given most of (but not all) validation studies using control procedures failed to confirm that ASD participants themselves were authoring the messages via FC, this method has been massively disputed and rejected. However, firm and definitive conclusions for/against FC’s validity require more robust demonstrations, particularly when considering the motor participation of both protagonists. We present here a case-report investigating the motor contribution of both protagonists during typing process using the non-invasive technique of accelerometry. A 17-year-old boy diagnosed with congenital deafness, ASD and developmental delay, and his facilitator, were equipped with small accelerometers fixed on their index finger, aimed at transforming index acceleration along the three spatial axes into electric signals. Typing on PC-keyboard was performed under three support conditions: Hand support, Forearm support, Elbow support, plus a Solo-typing condition. Accelerometric signals and video data were recorded during 4 FC sessions. We measured and compared the typing speed, the number/percentage of acceleration peaks produced by participant or by facilitator first, and those of ‘Signal under detection threshold’ in facilitator, the time offset between acceleration peaks of both protagonists, and the difference of amount of acceleration between them, across the different support conditions. Results indicate that in Hand support, most of the time, acceleration motions of participant’s index precede those of facilitator’s index. Then, the more distal the physical support (i.e. farer from the participant’s hand), the slower the speed of typing, the higher the percentage of ‘Signal under detection threshold’ in facilitator, the bigger the motor contribution from participant. Altogether, in all the support conditions, the participant’s authorship or, at least, co-authorship on the messages seems warranted. Finally, accelerometry seems relevant to objectivize authorship or co-authorship in FC and delineate various forms of FC.